Quality attributes of gluten free fried products from defatted peanut flour and starches of selected tropical roots and tubers - Adesina Adedeji R; Kajihausa Olatundun E; Sobukola Olajide P; Ololade Zacchaeus S (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
The aim of this study was to develop and evaluate gluten free fried products from defatted peanut flour and starches of common tropical roots. The result of the analysis showed that moisture content ranged from 3.52% to 5.89%; fat content ranged from 11.22% to 13.84%; crude fibre content ranged from 5.54% to 7.50%; colour (lightness) ranged from 22.21% to 69.88%; colour (redness) ranged from 9.95% to 26.54%;colour (yellowness) ranged from 10.15% to 43.17% and shrinkage ranged from 1.32% to 8.75%. The sample which was a composite of 90% sweet potato starch and 10% defatted peanut fried at 170 °C for 1 min had the lowest fat content. This study is very significant in meeting the demand in the management of celiac disease and gluten-related disorders, since gluten free diet is the only medically accepted treatment in resolving the challenge attributed to the consumption of foods containing gluten.